Implementation of Women's Representation Policy in the Recruitment of District Election Supervisory Committee (Panwascam) in Bekasi - Sabilla, Shafira Dewi; Rahayu, Susi Dian (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
Women's representation in politics is needed to be able to voice various kinds of women's aspirations, women's needs, and women's issues. As a form of support for women's political representation, the government has made special affirmation policies for women in politics, which include special quotas for women's candidacy in the DPR and DPRD, management and membership of women in political parties, and representation of women in election organizers. Although it has been regulated in the Election Law, which states that the composition of election organizers must pay attention to at least 30% of women's representation, in practice, until now, women's representation in election organizers has not been optimal, especially at the level of election organizers at the ad hoc level. This research focuses on the policy of women's representation in the recruitment of the Bekasi City District Panwaslu in 2023. This research uses the theory of policy implementation by Van Metter Van Horn using six variables: standards and objectives, resources, characteristics of the implementing organization, communication between implementing organizations, the attitude of the implementers, and the social, economic, and political environment. The result of this study is that currently the number of women in Panwascam Bekasi City is six (6) people, or 17% of the total 30 District election supervisory committee (Panwascam) members. Even though in the recruitment process, the Bekasi City Bawaslu has provided special affirmation policies for women, such as providing an extension of Panwascam registration time for sub-districts that have not met the quota of women. However, this does not necessarily increase women's representation in Panwascam. There are various obstacles faced by women, such as structural, cultural, and capability barriers.